Identification of human inflammatory dendritic cells - Segura, Elodie (Landes Bioscience, 2013)
Dendritic cells (DCs) are professional antigen-presenting cells that comprise several subsets with distinct phenotypes and functions, including inflammatory DCs that appear during inflammation. By analyzing human inflammatory fluids (arthritic synovial fluid and tumor ascites), we have identified the human equivalent of inflammatory DCs.